Research trends in vascular chips from 2012 to 2022: a bibliometrix and visualized analysis - Yang, Song; Luo, Jing; Zou, Wanwan; Zhu, Qikun; Cen, Jianzheng; Gao, Qiang (Frontiers in Bioengineering and Biotechnology, 2024)
Abstract Objective: The vascular chip has emerged as a significant research tool, garnering increasing interest and exploration. We utilize bibliometric techniques to analyze literature from the Web of Science (WOS) database, focusing on core journal publications. The aim is to provide a systematic review and prospective outlook on research trends within the vascular chip field, delving into current dynamics and highlighting areas for further investigation. Methods: We retrieved articles, proceedings papers, and early-access publications related to vascular chips published between January 2012 and December 2022 reported by Web of Science Core Collection (WoSCC) in 2023. Scientific bibliometric analysis was performed using R-bibliometrix, CiteSpace, VOSviewer, and Microsoft Excel software tools. Results: A total of 456 publications were obtained, including 444 articles, 11 proceedings papers, and 1 early-access article. These originated from 167 academic journals and 751 research institutions across 44 countries/regions. The United States contributed the majority of publications (41%), with Harvard University leading in contributions (6.6%). Lab on a Chip was the top journal in terms of publications. Notably, authors Jeon NL and Huh D wielded significant influence, with the former being the most prolific author and the latter garnering the most citations. Recent research has predominantly focused on angiogenesis in relation to endothelial cells. Conclusions: This scientometric investigation comprehensively surveys literature on vascular chips over past decade, providing valuable insights for scholars in the field. Our study reveals global increases in publications, with endothelial cells and angiogenesis being primary research focuses. This trend will persist, drawing continued attention from researchers.